Pharmacological inhibition of the F1‐ATPase/P2Y1 pathway suppresses the effect of apolipoprotein A1 on endothelial nitric oxide synthesis and vasorelaxation. (4th April 2019) - Cabou, Cendrine; Honorato, Paula; Briceño, Luis; Ghezali, Lamia; Duparc, Thibaut; León, Marcelo; Combes, Guillaume; Frayssinhes, Laure; Fournel, Audren; Abot, Anne; Masri, Bernard; Parada, Nicol; et al.
Abstract: Aim: The contribution of apolipoprotein A1 (APOA1), the major apolipoprotein of high‐density lipoprotein (HDL), to endothelium‐dependent vasodilatation is unclear, and there is little information regarding endothelial receptors involved in this effect. Ecto‐F1 ‐ATPase is a receptor for APOA1, and its activity in endothelial cells is coupled to adenosine diphosphate (ADP)‐sensitive P2Y receptors (P2Y ADP receptors). Ecto‐F1 ‐ATPase is involved in APOA1–mediated cell proliferation and HDL transcytosis. Here, we investigated the effect of lipid‐free APOA1 and the involvement of ecto‐F1 ‐ATPase and P2Y ADP receptors on nitric oxide (NO) synthesis and the regulation of vascular tone. Method: Nitric oxide synthesis was assessed in human endothelial cells from umbilical veins (HUVECs) and isolated mouse aortas. Changes in vascular tone were evaluated by isometric force measurements in isolated human umbilical and placental veins and by assessing femoral artery blood flow in conscious mice. Results: Physiological concentrations of lipid‐free APOA1 enhanced endothelial NO synthesis, which was abolished by inhibitors of endothelial nitric oxide synthase (eNOS) and of the ecto‐F1 ‐ATPase/P2Y1 axis. Accordingly, APOA1 inhibited vasoconstriction induced by thromboxane A2 receptor agonist and increased femoral artery blood flow in mice. These effects were blunted by inhibitors of eNOS, ecto‐F1 ‐ATPase and P2Y1 receptor. Conclusions: Using a pharmacological approach, we thus found that APOA1 promotes endothelial NO production and thereby controls vascular tone in a process that requires activation of the ecto‐F1 ‐ATPase/P2Y1 pathway by APOA1. Pharmacological targeting of this pathway with respect to vascular diseases should be explored.